MicroRNA-449a delays lung cancer development through inhibiting KDM3A/HIF-1α axis - Hu, Shan (J Transl Med, 2021)
BACKGROUND: It has been established that microRNA (miR)-449a is anti-tumorigenic in cancers, including lung cancer. Therefore, this study further explored miR-449a-mediated mechanism in lung cancer, mainly focusing on lysine demethylase 3A/hypoxia-induced factor-1α (KDM3A/HIF-1α) axis. METHODS: miR-449a, KDM3A and HIF-1α levels in lung cancer tissues and cell lines (A549, H1299 and H460) were measured. Loss- and gain-of-function assays were performed and then cell proliferation, cell cycle, apoptosis, invasion and migration were traced. The relationship between KDM3A, miR-449a and HIF-1α was verified. Tumor growth in vivo was also monitored. RESULTS: Both lung cancer tissues and cells exhibited reduced miR-449a and raised KDM3A and HIF-1α levels. miR-449a interacted with KDM3A; HIF-1α could bind with KDM3A. Up-regulating miR-449a hindered while suppressing miR-449a induced lung cancer development via mediating HIF-1α. Elevating KDM3A promoted cellular aggression while down-regulating KDM3A had the opposite effects. Up-regulating KDM3A or HIF-1α negated up-regulated miR-449a-induced effects on cellular growth in lung cancer. Restoring miR-449a impaired tumorigenesis in vivo in lung cancer. CONCLUSION: It is eventually concluded that miR-449a delays lung cancer development through suppressing KDM3A/HIF-1α axis. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12967-021-02881-8.